REPETISI DALAM AL-QURAN PERSPEKTIF AL-KARMANI - Munirah Munirah (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2017)
Repetition is a phenomenon of inside Qur’an. Many verses are repeated, the repetition is not aimless but it has many secrets. This article studied the book entitle Asra>r al-Takra>r Fi al-Qur’a>n by al-Karma>ni>. In that book, he mentioned the repetition verses specifically and explained the reasons and secrets. However, this book is not well known among the Islamic scholars. So, this book should be studied with scientific approach to find a knowledge of takra>r development in this era. The method is content analisys with historical and philosofical approach. With this method, I found some conclusions. First, Asra>r al-Takra>r fi> al-Qur’a>n is a interpretation linguistic book with comparative method. Second, takra>r in al-Karma>ni’s view is a part of mutasya>bihat verses, the repetition of verses equally, sometimes with addition or shorting. Thirt, the secrets of takra>rin al-Karma>ni’s view are to show i’jaz al-Qur’an, to corraberate the meaning before or explain it spesially, and also to glorify.